Effects of Pain Management Protocol on Pain Perception of Persons With Post-Operative Abdominal Surgery - พงศ์ชู, สมพร; ศรีธัญรัตน์, พัชรี; ฉาไธสง, ปิยะวดี; สอนพรหม, นิตยา; พันธ์จบสิงห์, จิราภรณ์; ชาติชำนิ, มนพร (Disease Control Journal, 2012)
This concurrent cohort aimed to investigate the effects of the evidence-based pain management protocol on pain perceptions of patients with post -operative abdominal surgery. This was data collected retrospectively in one group (n=30) during October 1, 2010- January 31, 2011 received usual nursing care and prospectively in experimental group (n=30) during February 1, - May 31, 2011 received education knowledge to patients intervention study. Descriptive Statistics were used to analyze subjects' characteristics. Independent t test and Fisher's Exact-test were used to test the differences between the 2 groups regarding age, and religion, marital status, occupation respectively. Mann-Whitney บ test was used to test the difference of pain perception at 24, 48, and 72 hours of the 2 groups Result showed that pain perception score at 24 and 48 hours post-surgery of the prospective group were significantly lower than that of the comparison group ( = 1.97, SD=2.39, p=.008, = 3.01, SD=2.63, p=.04 respectively). Nevertheless there was no significant difference at the 72 hours. It was suggested that future clinical study should be replicated in a similar population by improving dose and intensity of the program in order to confirming the effectiveness of this evidence -based protocol.